SCREENING OF EXTREMLY HALOPHILIC ARCHAEA FOR ITS BIOTECHNOLOGICAL POTENTIAL. - VAISHNAVI U. DIGASKAR; REBECCA S. THOMBRE; RADHIKA S. OKE (International Journal of Pharma and Bio Sciences, 2015)
Halophiles are salt loving organisms requiring about 3M- 5M NaCl concentration in their growth. Eleven halophilic archaea and nine bacteria were isolated from various samples from extremely high salt concentrated ecosystem from western parts of Maharashtra, India. The isolates were studied using morphological and biochemical studies. Most of the isolates were gram negative in nature. These organisms were tested for their ability to produce industrially important extracellular enzymes like caseinase, gelatinase, amylase, and protease. The current study indicates that, haloarchaea are of potential importance in pharmaceutical, industrial, textile and food industry.